Taxonomy and evolutionary history of the neotropical fern genus Salpichlaena (Blechnaceae) - G. G. Cárdenas; S. Lehtonen; H. Tuomisto (Naturalis Biodiversity Center, 2022)
Salpichlaena is a distinctive fern genus characterised by 2-pinnate climbing fronds with indeterminategrowth. The number of species in the genus has been a matter of debate. Taxonomic studies are made difficult by within-frond variability in pinna morphology and size, and by herbarium material being incomplete. We systematically documented 62 morphological traits in 283 herbarium specimens and sequenced 52 Salpichlaena and 11 outgroupspecimens. DNA sequences included plastid genes (rbcL, rpoC1 and rps4), intergenic spacers (rps4-trnS, trnH- psbA and trnG-trnR) and a nuclear gene (pgiC). Phylogenetic analyses based on the plastid markers divided the samples into six major clades. We recognise the three deepest clades as distinct species (S. hookeriana, S. papyrussp. nov. and S. volubilis), and each of the four shallower clades as a subspecies of S. volubilis. Furthermore, wesuggest that a group of specimens, placed into different clades in the plastid and nuclear trees and showing mixedmorphological characters, represent a fourth species of hybrid origin (S. hybrida sp. nov.). The most important di- agnostic characters are: degree of lamina reduction in fertile pinnules; pinna/pinnule apex incisions, pinna/pinnule margin thickness and lamina texture in sterile pinna/pinnules; presence or absence of foliar buds; shape of scales;and the appearance of the abaxial surface of the lamina (uniform or with stomata on small white protuberances).Each of the four species can be identified by several diagnostic characters, and their geographical ranges are broadand partly overlapping. In contrast, the subspecies are mostly allopatric and their morphological limits are diffuse.